Corruption and medicine in Latin America: a pilot study - Aparna Mathur; Roger Bate (American Enterprise Institute (AEI), 2017)
Fake and substandard medicines are a significant problem in developing nations and a growing problem in developed ones, too. This study finds that corruption is strongly correlated with poor-quality drugs.
Keywords: A; 330; global health; fake drugs; drug safety